Metformin; a review of its history and future: from lilac to longevity. Issue 1 (February 2017) - Thomas, Inas; Gregg, Brigid
Abstract : Metformin is a widely prescribed medication that has been used to treat children with type 2 diabetes in the United States for the past 15 years. Metformin now has a variety of clinical applications in pediatrics, and its potential clinical uses continue to expand. In addition to reviewing the current understanding of its mechanisms of action including the newly discovered effects on the gastrointestinal tract, we will also discuss current clinical uses in pediatrics, including in type 1 diabetes. Finally, we examine the existing state of monitoring for metformin efficacy and side effects and discuss prospective future clinical uses.